56.5k views
2 votes
How do you simplify
(√(2) +√(6) )/(√(8) + √(6) )?

User Jdweng
by
5.7k points

1 Answer

3 votes

The trick is to exploit the difference of squares formula,


a^2-b^2=(a-b)(a+b)

Set a = √8 and b = √6, so that a + b is the expression in the denominator. Multiply by its conjugate a - b:


(\sqrt8+\sqrt6)(\sqrt8-\sqrt6)=(\sqrt8)^2-(\sqrt6)^2=8-6=2

Whatever you do to the denominator, you have to do to the numerator too. So


(\sqrt2+\sqrt6)/(\sqrt8+\sqrt6)=((\sqrt2+\sqrt6)(\sqrt8-\sqrt6))/((\sqrt8+\sqrt6)(\sqrt8-\sqrt6))=\frac{(\sqrt2+\sqrt6)(\sqrt8-\sqrt6)}2

Expand the numerator:


(\sqrt2+\sqrt6)(\sqrt8-\sqrt6)=√(2\cdot8)+√(6\cdot8)-√(2\cdot6)-(\sqrt6)^2


(\sqrt2+\sqrt6)(\sqrt8-\sqrt6)=√(16)+√(48)-√(12)-6


(\sqrt2+\sqrt6)(\sqrt8-\sqrt6)=4+√(48)-√(12)-6


(\sqrt2+\sqrt6)(\sqrt8-\sqrt6)=-2+√(12)(\sqrt4-1)


(\sqrt2+\sqrt6)(\sqrt8-\sqrt6)=-2+√(12)(2-1)


(\sqrt2+\sqrt6)(\sqrt8-\sqrt6}=-2-√(12)

So we have


(\sqrt2+\sqrt6)/(\sqrt8+\sqrt6)=-\frac{2+√(12)}2

But √12 = √(3•4) = 2√3, so


(\sqrt2+\sqrt6)/(\sqrt8+\sqrt6)=-\frac{2+2\sqrt3}2=\boxed{-1-\sqrt3}

User Fat Shogun
by
6.3k points